2017
DOI: 10.1177/0363546517702863
|View full text |Cite
|
Sign up to set email alerts
|

Does an Injection of Adipose-Derived Mesenchymal Stem Cells Loaded in Fibrin Glue Influence Rotator Cuff Repair Outcomes? A Clinical and Magnetic Resonance Imaging Study

Abstract: This study revealed that an injection of adipose-derived MSCs loaded in fibrin glue during rotator cuff repair could significantly improve structural outcomes in terms of the retear rate. There were, however, no clinical differences in the 28-month period of follow-up. Although still in the early stages of application, MSC augmentation of surgical rotator cuff repair appears useful for providing an adequate biological environment around the repair site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 62 publications
2
153
0
Order By: Relevance
“…From a clinical standpoint, ASCs are easier and less invasive to harvest and are more abundant compared to other sources of MSCs . However, recent reports have not formed a consensus regarding efficacy of the ASC implantation on RTC healing in animal experiments as well as in clinical studies …”
Section: Summary Of Recent Reports On Adipose‐derived Stem Cell Implamentioning
confidence: 99%
See 2 more Smart Citations
“…From a clinical standpoint, ASCs are easier and less invasive to harvest and are more abundant compared to other sources of MSCs . However, recent reports have not formed a consensus regarding efficacy of the ASC implantation on RTC healing in animal experiments as well as in clinical studies …”
Section: Summary Of Recent Reports On Adipose‐derived Stem Cell Implamentioning
confidence: 99%
“…After antigen retrieval using proteinase K (PK; Sigma-Aldrich), donkey serum (Sigma-Aldrich) was added as a blocking agent. The slides were incubated with primary antibodies (rabbit monoclonal anti-collagen type I antibodies [1:100; Abcam]), followed by incubation with secondary antibodies (donkey anti-rabbit IgG [H þ L] whole antibodies [1:200; CFTM488 fluorescent reagents; Biotium, Fremont, 13 Clinical study Autologous human ASC, 4.46 M(average) Oh JH (2014) 14 Rabbit chronic RTC injury model Allogeneic rabbit ASC, 10 M Ineffective Lipner J(2015) 15 Rat acute RTC injury model Allogeneic rat ASC, 0.5 M Barco R (2015) 17 Rat acute RTC injury model Syngeneic rat ASC, 2 M Valencia Mora M (2014) 16 Rat acute RTC injury model Allogeneic rat ASC, 2 M 3 879 CA]). The slides were viewed under a fluorescence microscope (Keyence BZ-X700).…”
Section: Immunohistochemistry For Type I Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…In one, bMSCs applied during arthroscopic single-row rotator cuff repair drastically reduced retear rates at a 10-year followup. 113 A more recent study also found a significant decrease in retear rate after surgical augmentation with ASCs. 114 The paucity of clinical data from studies performed in the United States is largely due to the high risks associated with stem cell-based therapies, including growth of tumors, administration site reactions, and other adverse effects.…”
Section: Stem Cell-based Therapies For Rotator Cuff Repairmentioning
confidence: 89%
“…Two clinical studies provide insight into patient outcomes after surgical augmentation with MSCs. In one, bMSCs applied during arthroscopic single‐row rotator cuff repair drastically reduced retear rates at a 10‐year follow‐up . A more recent study also found a significant decrease in retear rate after surgical augmentation with ASCs .…”
Section: Stem Cell‐based Therapies For Rotator Cuff Repairmentioning
confidence: 92%